Pengaruh Implementasi Praktikum Virtual Lab Uji Golongan Darah Berbasis Android Terhadap Hasil Belajar Siswa - A. Iryanti (GENIUS: Jurnal Inovasi Pendidikan dan Pembelajaran, 2023)
This study aims to determine the effect of the implementation of android-based virtual lab practicum on student learning outcomes. This study used a Pre-Experimental method with a One-Group Pretest-Posttest Desgin design. Sampling using the purposive sampling technique, the samples in this study were students of class XI MIPA 1. The experimental class will be taught using an android-based virtual lab on blood type test material. The instrument used was a student activity observation sheet and a multiple choice test of 21 numbers that had been validated. The research data were analyzed descriptively and inferentially. Based on the results of data analysis, the average pretest learning outcome was 39,17 and posttest was 80,55 with the completeness of student learning outcomes after being given treatment of 79%. And the results of observing student activities with the implementation of android-based virtual lab practicum on blood type test material at the second meeting were in the very good category. The research data through the N-Gain test obtained an increase in student learning outcomes of 0,672 with a medium category. The data in this study were also tested for normality with the results of the data being proven normal and the One Sample T Test t test obtained Sig 0.000 < 0.05. The results of this study indicate that there is an effect of the implementation of the Android-Based Virtual Lab on student learning outcomes.